Pathway mapping as a tool to address police use of force in behavioral health crisis. (August 2022) - Ross, Heather M.; Pine, Kathleen H.; Curran, Sarah; Augusta, Dawn
Abstract: Police use of force is a significant problem in many communities, particularly related to episodes of behavioral health crisis where police are called to respond. Fragmentation of the behavioral health care system creates a revolving door where many residents with behavioral health challenges cycle in and out of the system, often accessing services via the 9-1-1 emergency system during a crisis episode. This work leverages ethnographic and participatory techniques to build a pathway map in order to represent and characterize the behavioral health crisis system in metropolitan Phoenix, Arizona, United States. Map findings illustrate that many nominally existing connections are functionally distant when viewed through the lens of a clinical handoff. The resulting pathway map can be used as a planning and confirmatory tool for community members, practitioners, and policymakers to address challenges in behavioral health and public safety. Highlights: Mental health crisis is frequently a factor in officer-involved shootings. Police report insufficient resources for people experiencing mental health crisis. Fragmented mental health systems lack effective handoffs between agencies. Qualitative pathway mapping enables quality improvement efforts in complex systems. Future statistical analysis can identify specific sites for system intervention.